Identification of Thermal Comfort of Opens Space in Soppeng Regency - Nurhasanah, Nurhasanah; Mulyadi, Rosady; Kusno, Asniawaty (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2023)
Thermal comfort is always associated with the climatic situation. Thermal comfort, known as a sense of comfort in thethermal situation in the surrounding environment, is also a necessity for space users. Open space is a place for spaceusers who must be able to create a comfortable situation, one of which is thermal comfort. Temperature, humidity, windvelocity, and radiation intensity are elements of the thermal environment, as well as human metabolism and clothinginsulation as human physical and physiological factors, are the six parameters of outdoor thermal comfort levelaccording to ASHRAE Standard. This research is a type of descriptive research that aims to explain the thermalconditions felt by the perpetrators of activities in one of the open spaces in the Soppeng Regency, the Ompo LakeTourism Area. The results obtained were from 349 respondents and as many as 216 respondents felt comfortable in themost comfortable temperature conditions in the range of 27.1 - 31˚C, with humidity > 70%, wind velocity 0.2 – 0.5 m/s,and radiation intensity <150 W/m2. Activity with a relaxed sitting (1 met) and moderate tropical clothes (0.3 – 0.5 clo).